Wahabi: Politik Agama dan Hasrat Kekuasaan di Indonesia - Erman Adia Kusumah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
This writing aims to find out the Wahabi movement in politics, da'wah, and education in Indonesia. In preparing this article the author uses the method of library study which includes collection methods systematic data from sources that contain information relating to the problem to be examined. The research results of the Wahabi-Salafi political movement developed in Indonesia since the reform era in various forms of propaganda spread by scholars of educational proceeds sponsored by Saudi Arabia, LIPIA has become the institution largest Wahabi educational the archipelago, Wahabi scholars have preached more sentiments towards other Islamic groups Wahabi-Salafi movement is a problem for the continuity of harmony among Muslims in the world, especially in Indonesia, this group disbanded many Islamic events such as Tahlilan, Maulid Nabi, Ashura which they considered as something Bid' ah and out of the path of Islam, Masyumi became the first vehicle of Whabi's vehicle in the political arena with main character their Muhammad Nasir but the party had to disband in 1960 after becoming a banned party, in the era after the Prosperous Justice Party reform became the second vehicle for this group to achieve power in Indonesia